Changing the culture of medical training: An important step toward the implementation of competency-based medical education. (3rd June 2017) - Ferguson, Peter C.; Caverzagie, Kelly J.; Nousiainen, Markku T.; Snell, Linda; ,
Abstract: Objective: The current medical education system is steeped in tradition and has been shaped by many long-held beliefs and convictions about the essential components of training. The objective of this article is to propose initiatives to overcome biases against competency-based medical education (CBME) in the culture of medical education. Materials and methods: At a retreat of the International Competency Based Medical Education (ICBME) Collaborators group, an intensive brainstorming session was held to determine potential barriers to adoption of CBME in the culture of medical education. This was supplemented with a review of the literature on the topic. Results: There continues to exist significant key barriers to the widespread adoption of CBME. Change in educational culture must be embraced by all components of the medical education hierarchy. Research is essential to provide convincing evidence of the benefit of CBME. Conclusions: The widespread adoption of CBME will require a change in the professional, institutional, and organizational culture surrounding the training of medical professionals.